The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1006/mthe.2000.0194
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-Mediated Suicide Gene Therapy for Ovarian Cancer

Abstract: The purpose of this phase I study was to determine the potential efficacy of adenoviral-mediated suicide gene therapy in women with recurrent ovarian cancer. Fourteen patients were treated intraperitoneally with herpes simplex virus-thymidine kinase (HSV-TK)-encoding adenovirus (AdHSV-TK) in dosages ranging between 1x10(9) and 1x10(11) pfu. Beginning 2 days later, ganciclovir (GCV) was administered intravenously at a dose of 5 mg/kg bid for 14 days. Transient vector-associated fever was experienced by 4 of 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 18 publications
1
56
0
1
Order By: Relevance
“…So far HSV 1 -tk/GCV gene therapy for ovarian cancer has being experimented with mostly in tumors transplanted into nude mice or syngeneic rats and made a great progress. [1][2][3][4] It is, however, important to emphasize that such an approach does not reflect the in vivo situation. DMBA-induced ovarian carcinogenesis provides a wellcontrolled experimental model of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far HSV 1 -tk/GCV gene therapy for ovarian cancer has being experimented with mostly in tumors transplanted into nude mice or syngeneic rats and made a great progress. [1][2][3][4] It is, however, important to emphasize that such an approach does not reflect the in vivo situation. DMBA-induced ovarian carcinogenesis provides a wellcontrolled experimental model of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…D espite recent advances in the chemotherapy of ovarian cancer, [1][2][3][4][5] only 73% of stage III and IV patients respond to therapy and overall prognosis remains poor. Therefore, alternative approaches are pursued to improve and prolong therapeutic effects in patients with the condition.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] There have been no reports evaluating this agent in NPC or head and neck cancer, both of which are common among Chinese people, often relapse locally and are often resistant to radiotherapy and chemotherapy. In this study, the majority of subjects had been diagnosed with NPC or head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I/II trials have subsequently been conducted using AdV/TK/GCV in a number of malignant tumors, including ovarian carcinoma, brain tumors, prostate cancer, hepatocellular carcinoma and so on. [9][10][11][12][13][14] All of these trials have shown that the approach is relatively safe, but efficacy has been localized to the injection site, which has limited its use. However, this treatment may be particularly suitable for some tumors that have the tendency to relapse locally, such as head and neck cancer or nasopharyngeal carcinoma (NPC).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recently, based on the fact that many human cancers are the result of accumulated genetic lesions that culminate in a transformed malignant phenotype, 3 investigation into the potential usefulness of gene therapy for peritoneal metastases has been initiated. 4 Numerous reports have described cancer gene therapy with intraperitoneal administration of viral gene carriers, [5][6][7][8][9][10][11][12][13][14][15][16] while there are only a few reports of intraperitoneal administration of DNA-cationic liposome complexes for gene transfer into intraperitoneal disseminated tumors. [17][18][19][20][21] Among the various gene carriers, viral vectors are the most widely used because of their efficiency.…”
Section: Introductionmentioning
confidence: 99%